1981
DOI: 10.1136/thx.36.8.596
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation of exercise to induce asthma?

Abstract: Bronchoconstriction was induced in asthmatic patients by means of isocapnic hyperventilation with dry air. Responses both within a day and between days did not differ significantly and corresponded closely with those observed after exercise. The mean fall in forced expiratory volume in one second (FEV1) observed with both techniques was equivalent to 36o%. Isocapnic hyperventilation with dry air, as used in this study, was a potent stimulus and provoked a reproducible response. The method was physically less d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the present study, moderate-, alternating (high/low)- and high-intensity warm-up strategies were chosen based on previous findings with hyperpnea [14,32] and with physical exercise warm-up trials [8,10]. According to a recent meta-analysis, most pronounced effects were expected to occur after interval and variable intensity respiratory warm-up since both continuous low- and high-intensity warm-up did not provide significant improvements [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, moderate-, alternating (high/low)- and high-intensity warm-up strategies were chosen based on previous findings with hyperpnea [14,32] and with physical exercise warm-up trials [8,10]. According to a recent meta-analysis, most pronounced effects were expected to occur after interval and variable intensity respiratory warm-up since both continuous low- and high-intensity warm-up did not provide significant improvements [13].…”
Section: Discussionmentioning
confidence: 99%
“…Isocapnic hyperventilation and exercise have been shown to produce closely correlated degrees of bronchoconstriction (Tweeddale et al, 1981;Deal et al, 1979). Craps et al (1978) reported inhibition of EIA following 4 days of treatment with ketotifen but this effect could not be confirmed by others following ketotifen given in single dose (Dorward & Patel, 1982), for 4 days (Kennedy et al, 1980), for 1 week (Lilja et al, 1983) or for 4 weeks (Petheram et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…At the start of the study IH was performed as previously described (Tweeddale et al, 1981). The target hyperventilation rate for each individual was set as the 4 min maximum voluntary ventilation (predicted from FEV1 by the formula of Clark et al, 1969).…”
Section: Methodsmentioning
confidence: 99%
“…This study compares the effect of inhaled verapamil and SCG in the prevention of asthma induced by isocapnic hyperventilation (IH) using a technique which has been shown to provoke the same degree of airflow limitation as 6-min exercise test [5].…”
Section: Introductionmentioning
confidence: 99%